Methodological and didactic problems of computer teaching methods in the study of electrotechnical disciplines - Korud, Vasyl (Видавництво Львівської політехніки, 2011)
Problematic questions of methodology and didactics, which arise while using computer leaching technologies In the study of electrotechnical disciplines are considered.
Keywords: computer teaching technologies; methodology; didactics; lecture; practical workshop; komputerowy technologii edukaclii; metodologia; wyklad; zajecie praktychne